Flexible pricing strategies and length of stay management during high demand volatility - Iutkina, Alla (Актуальні питання економічних наук, 2026)
The complexity of the operating conditions of hospitality enterprises, caused by changes in demand, intensification of competitive processes, and transformation of customer preferences, requires hospitality enterprises to implement adaptive management tools capable of ensuring a balance between revenue maximization and the rational use of available resources. The purpose of the article is to analyze and substantiate practical approaches to flexible pricing and length-of-stay management that increase the financial performance of hospitality businesses in conditions of high demand volatility. Methods. To achieve the set goal, a set of theoretical methods of scientific knowledge was used, in particular, analysis and synthesis to generalize scientific approaches, abstraction to identify key characteristics of demand volatility, and induction and deduction to form conclusions and practical recommendations. Results. Key factors influencing the volatility of demand in the national and regional hotel services markets include economic conditions, consumer socio-psychological expectations, seasonality, event activity, and price and competitive factors. It has been proven that effective demand management involves not only prompt tariff adjustments but also targeted regulation of the length of stay based on market dynamics, customer segment, and room stock occupancy. Analysis of modern pricing approaches, in particular dynamic pricing, market penetration strategies, and prestige pricing, enabled assessment of their effectiveness across consumer segments during periods of sharp demand fluctuations. Based on the results obtained, practical recommendations have been formulated for implementing integrated, flexible strategies that combine the automation of reservation management systems, segmental differentiation of tariffs, and the establishment of adaptive restrictions on the minimum and maximum length of stay. Conclusions. The use of adaptive pricing mechanisms, segmental demand management, and regulation of stay parameters ensures increased profitability, higher occupancy levels, and reduced risk of profit shortfalls, which together strengthen the competitiveness and financial stability of hospitality enterprises in a changing market environment.